Experimental host preference of diapause and non-diapause induced Culex pipiens pipiens (Diptera: Culicidae) - Faraji, Ary (Parasit Vectors, 2015)
BACKGROUND: Culex pipiens pipiens plays an important role in the transmission of several vector-borne pathogens such as West Nile virus (WNV) in North America. Laboratory and field studies suggest that this species is ornithophilic but because of genetic hybridization with sibling species during the active mosquito season, it may occasionally feed on mammals. Adult female Cx. p. pipiens undergo a facultative diapause and may serve as an overwintering mechanism for WNV. To determine the effect of diapause on the innate host preference of Cx. p. pipiens emerging from winter hibernation, we conducted host-choice experiments using bird and mammal hosts. METHODS: Mosquitoes were reared under non-diapause induced (NDI), diapause induced (DI), and field collected from overwintering (OW) hibernaculae. They were released into a large mesh enclosure housing two lard can traps, and given a choice between feeding on a dove or a rat. RESULTS: Host seeking Cx. p. pipiens were four times more likely to feed on the dove than the rat, regardless of experimental conditions. Under NDI conditions, Cx. p. pipiens were (p < 0.001) more attracted to the bird (79.9 % [75.6-84.1]) than the rat (20.1 [15.9-24.4]). Overwintering mosquitoes and those exposed to DI conditions were also significantly (p < 0.001) more attracted to birds (81.6 % [75.9-87.3]) than to rats (18.5 [12.7-24.2]). CONCLUSIONS: We provide new information about the innate host preference of Cx. p. pipiens emerging from diapause in temperate habitats where winter survival is crucial for disease transmission cycles. Although we showed that Cx. p. pipiens prefers an avian to a mammalian host, nearly 20 % of emerging mosquitoes in the spring could feed on mammals. Changes in host preferences may also contain valuable clues about transmission dynamics and subsequent timely interventions by vector control and public health practitioners.